Prevalence of physical activity levels and perceived benefits of and barriers to physical activity among Jordanian patients with coronary heart disease: A cross-sectional study - Alsaleh, Eman; Baniyasin, Faris (Frontiers in Public Health, 2023)
Background Many studies published in other countries have identified certain perceived benefits of and barriers to physical activity among patients with coronary heart disease. Nevertheless, there is no data about the issue relating to Jordanian patients with coronary heart disease. Objective This study aimed to describe the prevalence of levels of physical activity, the benefits of and barriers to physical activity as perceived by Jordanian patients with coronary heart disease, and the relationship between physical activity and perceived benefits of and barriers to physical activity. In addition, it focused on examining the influence of selected sociodemographic and health characteristics on physical activity and the perceived benefits of and barriers to physical activity. Methods A cross-sectional design was performed on a sample of 400 patients with coronary heart disease. They were given a list of perceived benefits of and barriers to physical activity and asked to what extent they disagreed or agreed with each. Results Jordanian patients with coronary heart disease perceived various benefits of and barriers to physical activity. Most of these benefits were physiologically related (average mean = 5.7, SD = 0.7). The most substantial barriers to physical activity as perceived by the patients were “feeling anxiety,” “not enough time,” “lack of interest,” “bad weather,” and “feeling of being uncomfortable.” Sociodemographic and health characteristics that significantly influenced perceived barriers to physical activity were age, gender, health perception, chest pain frequency, education, job, caring responsibilities, ability to travel alone, smoking, and previous and current physical activity behavior. Conclusion This study demonstrates that patients with coronary heart disease have perceived physiological benefits of physical activity and have perceived motivational, physical health, and environmental barriers to physical activity, which is significant in developing intervention strategies that aim to maximize patients' participation in physical activity and overcome barriers to physical activity.